Development of instant milk-based rice porridge with mung bean snack food guinataang munggo - Basman, Irene Camila Villareal; Azanza, Ma. Patricia (1997)
This research aims primarily to develop an acceptable instant coconut-milk based porridge with mung bean or guinataang munggo. This is in response to the growing demand to develop more processed rice-based products.The first phase of this study involved the selection of the acceptable recipe for guinataang munggo. Sensory evaluation showed that the recipe by Perez (1972) was the acceptable test recipe. Some modification, however, in the recipe was done to improve the consistency of the guinataang munggo. The standard formulation of the guinataang munggo consisted of the selected rice and mung bean cultivars compatible with the modified recipe. The ANOVA and DMRT results revealed that the most acceptable rice and mung bean cultivars for the standard recipe were Malagkit Sungsong and Pag-asa 7, respectively. The activities involved in the preparation of the instant guinataang munggo included preparation of the instant rice, preparation of dried mung bean, compounding the instant mix and rehydration of the instant product. The instant rice was prepared by soaking at 50°C for 30 min, cooking in an autoclave at 15 psi for 10 min, drying at 60-63°C for 55 min and puffing at 200°C for 4 min. Selection for the treatments were based on optimal percent ,moisture uptake, absence of chalky centers and highest puffing ratio obtained. Instant mung bean was prepared by roasting for 4 1/2 min, boiled for 20 min and dried at 60-63°C for 100 min. Sensory evaluation test was conducted to determine the most acceptable temperature and volume of water combination to rehydrate the instant product. The formulated instant guinataang munggo product consisted of instant rice and mung bean, cocopowder, sugar and carrageenan. It has a pH value of 6.8. The Aw values of 0.65 and 0.84 were recorded for processed and rehydrated product, respectively. The Yeast and Mold Count was <10 cfu/g for both processed and rehydrated instant product. The Total Plate Count were about 10^5 cfu/g and 10^3 cfu/g for the processed and rehydrated instant products, respectively. The cost of the instant guinataang munggo was computed at P6.95/ 50g with a 10% mark-
Thesis (BSFT)--University of the Philippines Dilim
Keywords: Snack foo; UPI